Integration of shari’ah governance framework in human resource management practice in Malaysia - Sahidon, Atirah; Hassan, Rusni; Abdullah, Shamsuddin; Salman, Syed Ahmed (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Abstract: The discussion on Shari`ah governance has gained significant attention and concerns in the Islamic finance industry. The Central Bank of Malaysia (BNM) introduced the Shari`ah Governance Framework for Islamic Financial Institutions (SGF) in 2010 for the purpose of promoting effective and good Shari`ah governance practices of Islamic Financial Institutions. The IFIs are expected to integrate necessary elements of good Shari’ah governance structure and processes in order to sustain their business in this complex environment as well as to ensure effective implementation of SGF through effective Human Resources Management (HRM). Many studies have been done on the Shariah governance aspects, processes and its effectiveness but not on the impact of HRM in SGF implementation. Therefore, the present study examines the SGF from HRM perspective particularly on the integration between SGF and HRM. It approached the topic from the perspective of job design and description through a literature review and a survey of professionals from the Shari`ah Division and HR Division of different types of IFIs in Malaysia. The data were collected from the literature review and survey responses from 78 respondents from different IFIs. The study found seven HRM scopes highlighted in the framework and found that the respondents’ general understanding of SGF implementation and HRM practices was satisfactory. Remarkably, it is also found that theIFIs have effectively used their HRM practices from the job design and description perspective as a tool to manage their key Shari`ah governance organs. Several limitations and recommendations were also presented to further enhance SGF implementation from this perspective.